2012
DOI: 10.1074/jbc.m111.321778
|View full text |Cite
|
Sign up to set email alerts
|

Small Amphipathic Molecules Modulate Secondary Structure and Amyloid Fibril-forming Kinetics of Alzheimer Disease Peptide Aβ1–42

Abstract: Background: A␤ aggregation may be modulated by small lipid-like molecules. Results: Activators induced ␤-structure and rapid aggregation, whereas inhibitors induced ␣-helical structure and small A␤ oligomers. Conclusion: Small lipid-like molecules modulate A␤ secondary structure and self-association at stoichiometric levels. Significance: Understanding the role of small molecules and lipids in Alzheimer disease is crucial for the development of effective therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 51 publications
4
49
0
Order By: Relevance
“…The effect of PBT2 on the aggregation of A␤1-42 was measured using a continuous ThT fluorescence assay described previously (McColl et al, 2009;Ryan et al, 2012Ryan et al, , 2013a. PBT2/CQ was prepared as a 1 mM stock in DMSO, and diluted into PBS containing ThT (10 M) to a final concentration of 10 M. A␤1-42 was added to a final concentration of 5 M, and the plate was incubated at 37°C, with shaking every 7 min, for 3 s, before the measurement of the ThT fluorescence intensity (444 nm excitation and 485 nm emission), using a Flexstation 3 Plate reader.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of PBT2 on the aggregation of A␤1-42 was measured using a continuous ThT fluorescence assay described previously (McColl et al, 2009;Ryan et al, 2012Ryan et al, , 2013a. PBT2/CQ was prepared as a 1 mM stock in DMSO, and diluted into PBS containing ThT (10 M) to a final concentration of 10 M. A␤1-42 was added to a final concentration of 5 M, and the plate was incubated at 37°C, with shaking every 7 min, for 3 s, before the measurement of the ThT fluorescence intensity (444 nm excitation and 485 nm emission), using a Flexstation 3 Plate reader.…”
Section: Methodsmentioning
confidence: 99%
“…To address this, we initially took advantage of inherent UV absorbance of the 8-HQ molecules, which provide an excellent tool to monitor the association of these compounds with A␤. Analyzing the absorbance unique to a species in solution, such as PBT2 or CQ, is a powerful tool to measure direct interactions, as exemplified by studies investigating the interaction of 7-nitrobenz-2-oxa-1,3-diazol-4-yl aminolabeled phospholipids with apoC-II (Mok et al, 2011;Ryan et al, 2011), or the interaction of Alexa-488 labeled DNA with Klenow fragment (Bailey et al, 2009). PBT2 and CQ are particularly suited to this approach because they have a low molecular mass and do not sediment effectively in the aqueous-based buffer systems of the experiment.…”
Section: Analysis Of the Interaction Of 8-hq With A␤mentioning
confidence: 99%
See 1 more Smart Citation
“…PP-2A is a protein phosphatase widely present and conservative in cells, which can catalyze in vivo dephosphorylation of the phosphorylated site of the substrate (15). A number of reports have demonstrated that the activity of PP-2A in AD patients was decreasing (16).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a parallel study using the same compound library with amyloid-β peptides displayed a quite different pattern of activators and inhibitors. This indicates that the pattern of activation and inhibition observed with apoC-II is specifi c to this protein, and should not be generalised to other amyloidforming proteins (Ryan et al 2012 ).…”
Section: The Effects Of Hydrophobic "Lipid-like" and Detergent Moleculesmentioning
confidence: 97%